Analysis of photovoltaic system performance time series: Seasonality and performance loss. (May 2015) - Phinikarides, Alexander; Makrides, George; Zinsser, Bastian; Schubert, Markus; Georghiou, George E.
Abstract: In this work, the seasonality and performance loss rates of eleven grid-connected photovoltaic (PV) systems of different technologies were evaluated through seasonal adjustment. The classical seasonal decomposition (CSD) and X-12-ARIMA statistical techniques were applied on monthly DC performance ratio, R P, time series, constructed from field measurements over the systems' first five years of operation. The results have shown that the R P of crystalline silicon (c-Si) technologies was higher during winter. This was also the case for the copper–indium gallium-diselenide (CIGS) and cadmium telluride (CdTe) technologies but with lower seasonal amplitude. The amorphous silicon (a-Si) technology exhibited a different seasonal profile, with high R P during summer and autumn and low during winter. In addition, the trends extracted from the application of CSD and X-12-ARIMA on three-year, four-year and five-year R P time series were used to estimate linear performance loss rates. A comparison between standard linear regression (LR), CSD and X-12-ARIMA has shown that CSD and X-12-ARIMA resulted in higher rates overall for c-Si, 1.07 and 0.93%/year respectively, but with significantly less uncertainty than LR. Lastly, it was shown that X-12-ARIMA provided statistical inference in the presence of outliers and produced model residuals that were uncorrelated, in contrast to CSD. Highlights: Seasonal decomposition of the performance of eleven grid-connected PV technologies. Statistically significant estimates through X-12-ARIMA. Lower seasonal component standard deviation for thin-film technologies. Mean performance loss rate of 0.93%/year for crystalline silicon technologies. Higher mean performance loss rate for thin-film technologies.